Effect of an android-based KEKASIH class on breastfeeding knowledge, attitudes, and breastfeeding self-efficacy among pregnant women in Bengkulu City - Epti Yorita; Rina; Mariati; Rolita Efriani; Sri Yanniarti (Alma Ata University Press, 2026)
Background: Exclusive breastfeeding coverage remains suboptimal in many regions in Indonesia, including Bengkulu City. This is related to several factors, such as pre-lacteal feeding practices, limited maternal knowledge, inadequate family support, and cultural influences. Strengthening breastfeeding education during pregnancy is essential to improve maternal preparedness and support successful exclusive breastfeeding. Objectives: This study aimed to examine the effect of an Android-based KEKASIH Class educational program on breastfeeding knowledge, attitudes, and breastfeeding self-efficacy among pregnant women. Methods: A quasi-experimental study with a non-equivalent control group design was conducted among 70 third-trimester pregnant women in Bengkulu City. Participants were selected using purposive sampling and divided into an intervention group and a control group. The intervention group received breastfeeding education through the Android-based KEKASIH Class application, while the control group received conventional education through antenatal classes. Data were analyzed using univariate analysis and non-parametric tests, including the Wilcoxon signed-rank test and the Mann–Whitney U test. Results: The results showed significant improvements in breastfeeding knowledge, attitudes, and breastfeeding self-efficacy in both groups after the intervention (p < 0.05).There was no statistically significant difference between the intervention and control groups (p > 0.05), indicating that both educational approaches were effective in improving maternal readiness for breastfeeding. Conclusions: The findings demonstrate that both the Android-based KEKASIH Class and conventional antenatal education can effectively improve breastfeeding knowledge, attitudes, and breastfeeding self-efficacy among pregnant women. Digital health education can therefore be considered an alternative strategy to support breastfeeding promotion programs.